Docking Study of Naringin Binding with COVID-19 Main Protease Enzyme - Amin Huseen, Narmin H. (Iraqi Journal of Pharmaceutical Sciences, 2020)
The Coronavirus Disease (COVID-19) has recently emerged as a human pathogen caused by SARS-CoV-2 virus was first reported from Wuhan, China, on 31 December 2019. Upon study, it has been used molecular docking to binding affinity between COVID-19 protease enzyme and flavonoids with evaluations based on docking scores calculated by AutoDock Vina. Results showed that naringin suppressed COVID-19 protease, as it has the highest binding value than other flavonoids including quercetin, hesperetin, garcina and naringenin. An important finding in this study is that naringin with neighboring poly hydroxyl groups can serve as inhibitors of COVID-19 protease bind to the S pocket of protein, it is shown that residues His163, Glu166, Asn142, His41and PHe181 participate in the hydrogen bonding and pi-pi interactions, the same as happened with decahydroisoquinolin as a novel scaffold for SARS 3CL protease inhibitors.In other hand, some of the known protease inhibitors and anti-influenza drugs docked with COVID-19 protease, it has low binding value than naringin